(3Gdehabjs - (3eMeO Hf CMeO Hf EHQGgje, CHh GdMSf, GdeYQha HGHf cjSGf,J (B299 (3g` s
(3ChdgG (B:s
(3bGd dj GHf MHGf WdH Gdehab TjFkG ef eNJUQGJ GdfMh abjd dg ZjQ cJGH bGd CHhGdMSf acdefG HGYOGO gPG GdcJGH s
(3BNQgG (B:s
(3Ch jVGa GdHYV Edi Gdcd GddGe hef, cbhdc KhH NR Cj KhH ef NR hZdGe RjO Cj ZdGe dRjO Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B308 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B213s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B170 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B322 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI (B((3JGecQhO (B2/3) (3HGdQHGW (B(40) s
Keywords: (3GdfMhs